Biomass-based hard carbon negative electrode material, preparation method thereof and sodium ion battery

By pretreating the biomass raw materials with a low eutectic solvent system and high melting point metal nitrate under pH of 1.0-5.0, and calcining them in sections under an inert atmosphere, a hard carbon negative electrode material with optimized structure was prepared, which solved the problem of low energy storage of biomass-based hard carbon negative electrode material, and achieved the effects of high specific capacity, good rate performance and long cycle life.

CN119873801AActive Publication Date: 2025-04-25SUZHOU UNIV

Patent Information

Application Number
CN202510372023.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

The existing biomass-based hard carbon anode materials have a large number of structural defects and open pore structures, resulting in low energy storage.

Method used

By using low-melting metal chloride salt and acid solution to form a low-eutectic solvent system under pH of 1.0-5.0, combined with the introduction of high-melting metal nitrate, the biomass raw material is pretreated, and then calcined in a segmented atmosphere under an inert atmosphere to prepare a hard carbon negative electrode material.

Benefits of technology

This method effectively regulates the interlayer structure and defects of hard carbon negative electrode materials, improves its specific capacity, rate performance and cycle stability, reduces irreversible capacity losses, and improves the first-time Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873801A_ABST
    Figure CN119873801A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass-based hard carbon negative electrode material, a preparation method thereof and a sodium ion battery, and relates to the technical field of battery energy storage. The preparation method comprises the following steps that a first mixed solution is prepared and obtained, the first mixed solution comprises low-melting-point metal chlorate, high-melting-point metal nitrate, acid liquor and a water solvent, and the pH value of the first mixed solution is any one of 1.0-5.0; adding a biomass raw material into the first mixed solution, and uniformly mixing to obtain a second mixed solution; sequentially carrying out suction filtration and drying on the second mixed solution to prepare a biomass precursor; and placing the biomass precursor in inert protective gas, carrying out segmented calcination on the biomass precursor, and sequentially crushing and sieving the calcined product to prepare the hard carbon negative electrode material. The structure defect and the open pore structure of the prepared hard carbon negative electrode material are optimized, so that the sodium ion energy storage performance and the first-round coulombic efficiency of the hard carbon negative electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery energy storage, and in particular to a biomass-based hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] High-performance negative electrode materials are one of the key factors in promoting the industrialization of sodium-ion batteries. Among the many negative electrode materials, hard carbon has become the most widely used negative electrode material for sodium-ion batteries due to its advantages such as rich carbon sources, high sodium storage capacity and low cost. The precursors of hard carbon come from a wide range of sources and can be mainly divided into two categories: polymer materials and biomass. Compared with polymer materials, biomass precursors are not only lower in cost and more widely available, such as carbohydrates, starch, protein, cellulose, hemicellulose and lignin, but also can retain their unique morphology and structure during the carbonization process, providing more possibilities for the design and optimization of negative electrode materials for sodium-ion batteries.

[0003] In the prior art, the hard carbon prepared has a high sodium storage capacity, a low working potential and excellent cycle stability. Its microstructure shows a highly disordered feature, which is composed of anisotropic graphite-like microcrystals randomly stacked and has a low degree of crystallinity. This unique structure allows hard carbon to have a larger interlayer spacing, and at the same time there are more structural defects and a larger specific surface area. These characteristics are not only conducive to the embedding and de-embedding of sodium ions, but also have an important influence on the formation process of the solid electrolyte interface film. However, the large number of defects and open pores in the hard carbon structure also bring some challenges. For example, during the first charge and discharge process, these defects and pores are prone to consume too much electrolyte to form "dead sodium" sites, resulting in additional irreversible capacity loss, thereby reducing the first coulombic efficiency of the hard carbon. Summary of the invention

[0004] One object of the first aspect of the present invention is to provide a method for preparing a biomass-based hard carbon negative electrode material to solve the technical problem in the prior art that a large number of structural defects and open pore structures of biomass-based hard carbon negative electrode materials lead to low energy storage.

[0005] Another object of the first aspect of the present invention is to further improve the dispersion stability of metal ions.

[0006] The second aspect of the present invention aims to provide a hard carbon negative electrode material, which is prepared according to the above preparation method.

[0007] The third aspect of the present invention aims to provide a sodium ion battery comprising the hard carbon negative electrode material prepared by the above preparation method.

[0008] According to the purpose of the first aspect of the present invention, the present invention provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: Prepare a first mixed solution, wherein the first mixed solution includes a low melting point metal chloride, a high melting point metal nitrate, an acid solution and an aqueous solvent, and the pH of the first mixed solution is any value between 1.0 and 5.0; Adding the biomass raw material to the first mixed solution and mixing them evenly to prepare a second mixed solution; The second mixed solution is filtered and dried in sequence to prepare a biomass precursor; The biomass precursor is placed in an inert protective gas and calcined in stages, and the calcined products are crushed and sieved in sequence to prepare the hard carbon negative electrode material; wherein: The low melting point metal chloride and the acid solution form a low eutectic solvent system, the melting point of the metal ions in the low melting point metal chloride is lower than 650°C, the melting point of the metal ions in the high melting point metal nitrate is higher than 1100°C, and the calcination temperature of the staged calcination includes a first temperature and a second temperature, the first temperature is any value between 400°C and 800°C, and the second temperature is any value between 1100°C and 1600°C.

[0009] Optionally, the low melting point metal chloride salt is any one or more of tin chloride, zinc chloride, gallium chloride, aluminum chloride, sodium chloride, potassium chloride, and lead chloride; The high melting point metal nitrate is any one or more of titanium nitrate, zirconium nitrate, molybdenum nitrate, vanadium nitrate, chromium nitrate, niobium nitrate and iron nitrate.

[0010] Optionally, the molar ratio of the low melting point metal chloride, the high melting point metal nitrate, the acid solution and the water solvent in the first mixed solution is any value of (0.01-5):(0.001-10):(0.1-10):1.

[0011] Optionally, the acid solution is any one or more of hypochlorous acid, hydrochloric acid, sulfuric acid, sulfurous acid, acetic acid, formic acid, citric acid, and phosphoric acid.

[0012] Optionally, the pH of the first mixed solution is any value between 1.0 and 3.0.

[0013] Optionally, before the step of sequentially filtering and drying the second mixed solution to prepare the biomass precursor, the following step is further included: The second mixed solution is mechanically activated by high-energy ball milling, and the mechanical activation time is any value in the range of 0.1 h to 6 h.

[0014] Optionally, the biomass raw material is any one or more of bamboo, wood, reed, coffee grounds, bagasse, cotton stalks, hemp stalks, wheat straw, rice straw, corn stalks, corn cobs, coconut shells, durian shells, rice husks, walnut shells, peanut shells, hazelnut shells, starch, and lignin.

[0015] Optionally, the mass ratio of the biomass raw material in the second mixed solution to the first mixed solution is any value in the range of 0.01-5:1.

[0016] According to the purpose of the second aspect of the present invention, the present invention also provides a biomass-based hard carbon negative electrode material, which is prepared according to any of the above-mentioned methods for preparing the hard carbon negative electrode material.

[0017] According to the purpose of the third aspect of the present invention, the present invention also provides a sodium ion battery, comprising a hard carbon negative electrode material prepared by the preparation method of the hard carbon negative electrode material described in any of the above items, wherein the sodium ion battery has an initial discharge specific capacity higher than 389 mAh / g, an initial coulombic efficiency greater than 94.5%, and a capacity retention rate after 2000 cycles higher than 92.25%.

[0018] The present invention forms a low eutectic solvent system by combining a low melting point metal chloride with an acid solution, and introduces a high melting point metal nitrate to pretreat the biomass raw material under the condition of a pH value of 1.0-5.0. The chemical composition and microstructure of the biomass precursor can be precisely regulated, and the dissolution of non-carbon components in the biomass raw material and the optimization of the pore structure can be promoted. The interlayer structure ordering, defect regulation, closed pore generation and conductivity improvement of the hard carbon negative electrode material can be ensured through staged calcination under an inert atmosphere. After crushing and sieving, a hard carbon negative electrode material with uniform particle size and optimized structure is prepared, which effectively improves its specific capacity, rate performance and cycle stability, reduces irreversible capacity loss, and improves the first coulomb efficiency, making it more suitable for high-performance sodium ion batteries.

[0019] Furthermore, the present invention sets the pH at any value between 1.0 and 3.0 so that the acid solution in the low eutectic solvent provides a stronger hydrogen bonding effect, that is, the low melting point metal chloride is more stable as a hydrogen bond acceptor, and the high melting point metal nitrate can maintain a higher solubility to avoid the formation of hydroxide precipitation, so that the viscosity of the low eutectic solvent is reduced, the fluidity is enhanced, and the solubility is improved, so that it can more effectively penetrate and act on the biomass raw materials, improve its shear and solubility, further weaken the hydrogen bond network of cellulose, reduce the crystallinity, thereby reducing the collapse of amorphous carbon, making the hard carbon structure more uniform, and improving the cycle stability.

[0020] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings: Figure 1 is a schematic flow chart of a method for preparing a hard carbon negative electrode material according to an embodiment of the present invention; Figure 2 is the XRD spectrum of the hard carbon negative electrode material prepared according to Example 1 of the present invention; Figure 3 is a SEM image of the hard carbon negative electrode material prepared according to Example 1 of the present invention; Figure 4 is the first cycle discharge curve of the sodium ion battery of the hard carbon negative electrode material prepared according to Example 1 of the present invention; Figure 5 is the first cycle discharge curve of the sodium ion battery of the hard carbon negative electrode material prepared according to Comparative Example 1 of the present invention; Figure 6 is the first cycle discharge curve of the sodium ion battery of the hard carbon negative electrode material prepared according to Comparative Example 2 of the present invention; Figure 7 This is the first cycle discharge curve of the sodium ion battery using the hard carbon negative electrode material prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0022] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0023] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0024] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0026] Figure 1 is a schematic flow chart of a method for preparing a hard carbon negative electrode material according to an embodiment of the present invention.

[0027] like Figure 1 As shown, the present invention provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: Step S100: preparing a first mixed solution, the first mixed solution comprising a low melting point metal chloride, a high melting point metal nitrate, an acid solution and an aqueous solvent, and the pH of the first mixed solution is any value between 1.0 and 5.0; Step S200: adding the biomass raw material to the first mixed solution, and mixing them evenly to prepare a second mixed solution; Step S300: filtering and drying the second mixed solution in sequence to obtain a biomass precursor; Step S400: placing the biomass precursor in an inert protective gas and calcining it in stages, and crushing and sieving the calcined products in turn to prepare a hard carbon negative electrode material, wherein a low-melting-point metal chloride and an acid solution form a low-melting-point eutectic solvent system, the melting point of the metal ions in the low-melting-point metal chloride is lower than 650°C, and the melting point of the metal ions in the high-melting-point metal nitrate is higher than 1100°C, and the calcination temperature of the staged calcination includes a first temperature and a second temperature, the first temperature is any value between 400°C and 800°C, and the second temperature is any value between 1100°C and 1600°C.

[0028] In the present embodiment, in the preparation method of the hard carbon negative electrode material, firstly, a first mixed solution including a low melting point metal chloride, a high melting point metal nitrate, an acid solution and an aqueous solvent is prepared, then the biomass raw material is added to the first mixed solution, and after mixing evenly, a second mixed solution is prepared, and the second mixed solution is filtered and dried in sequence to prepare a biomass precursor, and then the biomass precursor is placed in an inert protective gas and calcined in stages, and the calcined product is crushed and sieved in sequence to prepare a hard carbon negative electrode material. Among them, the low melting point metal chloride and the acid solution form a low eutectic solvent system, and the calcination temperature of the staged calcination includes a first temperature and a second temperature, the first temperature is any value in the range of 400°C-800°C, that is, the first temperature can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, or any value in the range of 400°C-800°C, and the second temperature is any value in the range of 1100°C-1600°C. A value, that is, the second temperature can be 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, or any value between 1100°C and 1600°C, and the pH of the first mixed solution is any value between 1.0 and 5.0, that is, the pH of the first mixed solution can be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5 or 5.0, or any value between 1.0 and 5.0.

[0029] In this embodiment, a low eutectic solvent system is formed by a low melting point metal chloride and an acid solution, combined with the introduction of a high melting point metal nitrate, and the biomass raw material is pretreated at a pH of any value between 1.0 and 5.0. This can accurately regulate the chemical composition and microstructure of the biomass precursor, promote the dissolution of non-carbon components in the biomass raw material and optimize the pore structure, and through staged calcination under an inert atmosphere, ensure the ordering of the interlayer structure, defect regulation, closed pore generation and conductivity improvement of the hard carbon negative electrode material. After crushing and screening, a hard carbon negative electrode material with uniform particle size and optimized structure is prepared, which effectively improves its specific capacity, rate performance and cycle stability, reduces irreversible capacity loss, and improves the first coulombic efficiency, making it more suitable for high-performance sodium ion batteries.

[0030] In this embodiment, under the first temperature condition, the low melting point metal melts to fill the pores of the cellulose formed after the biomass raw material is hydrolyzed, and the high melting point metal forms a metal oxide for stabilizing the carbon structure. The melted low melting point metal can act as a dispersant to promote the uniform distribution of the high melting point metal oxide, so as to improve the etching uniformity of the high melting point metal oxide in the carbon material under the second temperature condition. Under the second temperature condition, the molten low melting point metal is further vaporized and forms uniformly distributed nanopores in the carbon material, thereby increasing the specific surface area of ​​the hard carbon negative electrode material. The high melting point metal oxide is carbon-thermally reduced to form nanopores, further increasing the sodium storage sites of the hard carbon negative electrode material. At the same time, the vaporization etching of the low melting point metal can improve the reduction etching effect of the high melting point metal oxide, so that the pore structure distribution in the carbon material is more uniform, so that the sodium ion battery based on the hard carbon negative electrode material has both high capacity, low specific surface area, high rate performance and long cycle life.

[0031] In this embodiment, the low eutectic metal chloride salt acts as a hydrogen bond acceptor and the acid liquid acts as a hydrogen bond donor. The two are mixed to form a low eutectic solvent system. The low eutectic solvent system can accurately tailor the cell structure of the biomass raw material, thereby realizing closed pores in the hard carbon derived therefrom, that is, the low eutectic solvent effectively changes the pore structure by simultaneously shearing and dissolving the amorphous components to form closed pores of adjustable size. At the same time, the highly active chloride ions in the low eutectic solvent system have a strong charge effect and can form stable hydrogen bonds with the hydroxyl groups in the cellulose molecules, thereby effectively shearing the originally tight hydrogen bond network structure in the cellulose crystal region and regulating the crystallinity of cellulose. In addition, the cellulose molecules can exhibit certain alkaline characteristics in the solvent system, or exist in a protonated form, and the lone pair of electrons in the molecule can coordinate with the Lewis acid, and the metal ions, as typical Lewis acid cations, can interact with the electron donor sites in the cellulose molecules, further weakening the hydrogen bonding forces inside the cellulose macromolecules. This dual action mechanism not only significantly reduces the crystallinity of cellulose, but also achieves precise regulation of cellulose, which helps to form a closed pore structure, reduce irreversible capacity loss, promote the formation of micropores and interlayer defects, improve sodium ion storage capacity, and enhance cycle stability.

[0032] In this embodiment, the acid component in the low eutectic solvent system can not only purify the biomass precursor and remove inorganic impurities in the biomass precursor, but also simultaneously remove part of the lignin and hemicellulose, thereby increasing the cellulose content in the biomass precursor. It also acts as an oxidant to introduce oxygen-containing functional groups such as carbonyl and hydroxyl groups into the derived hard carbon, significantly improving the sodium storage performance of the hard carbon material. At the same time, the nitrate in the high melting point metal nitrate reacts with cellulose to obtain nitrocellulose, thereby introducing nitro groups and the like. In the subsequent carbonization, the groups escape, increasing the overall etching of the graphite layer, thereby playing a role in pore formation. The cellulose is converted into a rich short-range ordered carbon layer, which effectively closes the open pores generated during the pyrolysis process. By regulating the components of the biomass precursor through chemical treatment, the microstructure of the derived hard carbon can be controlled. The resulting hard carbon negative electrode material will have a higher degree of graphitization, a lower specific surface area and oxygen content, that is, the hard carbon negative electrode material with the above structural characteristics has a large number of sodium ion intercalation sites and fewer irreversible sodium storage sites, and the reversible sodium storage capacity of the hard carbon negative electrode material will be improved. The mechanical activation method can significantly reduce the particle size of the material, increase the specific surface area, thereby providing more active sites, enhancing the reaction activity of the material, and increasing the energy state of the material, making it easier to participate in electrochemical reactions.

[0033] In this embodiment, the pH of the first mixed solution is any value between 1.0 and 5.0. By setting the acidic condition of the first mixed solution within the above range, not only can a stable low eutectic solvent system be formed, the shear force of the low eutectic solvent be increased, and the hydrolysis of biomass raw materials into cellulose be promoted, but also the solubility of metal ions in low-melting-point metal chlorides and high-melting-point metal nitrates be increased, and the metal ions are prevented from forming insoluble hydroxides or precipitations, and the metal ions are prevented from forming complexes with chloride ions, thereby further improving the dispersion uniformity of the metal ions.

[0034] In this embodiment, the first temperature is any value between 400°C and 800°C, and the second temperature is any value between 1100°C and 1600°C. By setting the first temperature and the second temperature within the above-mentioned corresponding ranges, the low-melting-point metal in the low-melting-point metal chloride is completely melted under the first temperature condition, so that the molten low-melting-point metal can be evenly attached to the surface of the carbon material, and at the same time, it acts as a dispersant to evenly disperse the high-melting-point metal oxide formed under the first temperature condition. Under the second temperature condition, the low-melting-point metal is vaporized and etched to form nanopores in the carbon material, and at the same time, the high-melting-point metal oxide is carbon-thermally reduced to form evenly distributed nanopores in the carbon material, thereby further increasing the specific surface area of ​​the hard carbon negative electrode material.

[0035] In this embodiment, by using the first mixed solution to pretreat the biomass raw material, a one-step pyrolysis method is used to prepare high-performance hard carbon negative electrode materials. Compared with the traditional two-step carbonization method, it has significant process advantages and economy, simplifies the preparation process, avoids the separation of intermediate products and secondary heat treatment, and reduces energy consumption by about 30%-40%, while shortening the production cycle by more than 50%. In addition, the one-step pyrolysis method can better control the microstructure of the hard carbon negative electrode material, so that it has a higher specific surface area, more uniform pore distribution and better electrochemical performance, providing a more efficient and environmentally friendly preparation method for the application of hard carbon negative electrode materials in sodium ion batteries, supercapacitors and other fields.

[0036] In a further embodiment, the low melting point metal chloride is any one or more of tin chloride, zinc chloride, gallium chloride, aluminum chloride, sodium chloride, potassium chloride, and lead chloride, and the high melting point metal nitrate is any one or more of titanium nitrate, zirconium nitrate, molybdenum nitrate, vanadium nitrate, chromium nitrate, niobium nitrate, and iron nitrate. In this embodiment, the melting point of the low melting point metal is lower than 650°C, and the melting point of the high melting point metal is higher than 1100°C. A first mixed solution is prepared by mixing a low-melting-point metal chloride, a high-melting-point metal nitrate and an acid solution, so that the low-melting-point metal and the high-melting-point metal in the first mixed solution are simultaneously attached to the cellulose formed by the hydrolysis of the biomass raw material, and when calcined at a first temperature, the low-melting-point metal is melted by heat and attached to the surface of the carbon material, and the high-melting-point metal reacts to form a high-melting-point metal oxide and is uniformly attached to the surface of the carbon material through the dispersion of the molten low-melting-point metal, so that when calcined at a second temperature, the low-melting-point metal is vaporized and etched to form nanopores, and the high-melting-point metal oxide is carbon-thermally reduced to form nanopores, thereby increasing the specific surface area of ​​the hard carbon negative electrode material, optimizing the pore structure of the hard carbon negative electrode material, and increasing the sodium storage performance of the hard carbon negative electrode material, thereby improving the charge and discharge specific capacity of the sodium ion battery based on the hard carbon negative electrode material.

[0037] In a further embodiment, the molar ratio of the low melting point metal chloride, the high melting point metal nitrate, the acid solution and the water solvent in the first mixed solution is any value of (0.01-5): (0.001-10): (0.1-10): 1. In this embodiment, by setting the molar ratio of the low melting point metal chloride, the high melting point metal nitrate, the acid solution and the water solvent within the above range, the low eutectic metal chloride and the acid solution form a stable low eutectic solvent system, and the acid solution and the water solvent form an acidic condition with a pH of 1.0-5.0, so that the low eutectic solvent system can fully hydrolyze the biomass raw material to form cellulose, destroy the hydrogen bond network structure of cellulose, reduce the crystallinity of cellulose, and at the same time ensure the uniformity of the dispersion of the various metal ions in the first mixed solution to prevent precipitation or complex formation.

[0038] In this embodiment, the interlayer spacing and micropore size of graphite crystallites can be controlled by controllably adjusting the type and concentration of metal ions, thereby comprehensively regulating the interface / bulk electrochemistry of hard carbon. Metal ions within the above concentration range can catalyze the growth of graphite sheets into long-range ordered graphene sheets. At high temperatures, metal ions break the sp3 carbon bridges between graphene sheets, allowing the graphene sheets to rearrange freely to form nanographite domains and carbon micropores, and promote the removal of irreversible oxygen-containing defects through the coordination between metal catalytic ions and oxygen-containing defects. The optimized hard carbon has expanded graphite regions and highly developed nanopores, which reduces the defect content and is conducive to the rapid storage of sodium ions. At the same time, MN 4 -C (M is a metal atom) structure can catalyze NaPF 6 The rapid decomposition of graphite results in a thin and inorganic-rich solid electrolyte interphase and fast interfacial sodium-ion storage kinetics, and triggers a local electric field within the graphite domain, providing a Coulomb force to reduce the diffusion barrier to accelerate the bulk sodium-ion storage kinetics.

[0039] In a further embodiment, the acid solution is any one or more of hypochlorous acid, hydrochloric acid, sulfuric acid, sulfurous acid, acetic acid, formic acid, citric acid, and phosphoric acid. In this embodiment, when the acid solution is a strong acid, that is, when the acid solution is hydrochloric acid or sulfuric acid, it helps to improve the solubility of high melting point metal nitrates and prevent the formation of hydroxide precipitation in the solution. When the acid solution is a weak acid, that is, the acid solution is acetic acid or citric acid, it can form a stable metal organic complex with metal ions, improve the uniformity of metal ion dispersion in the solvent, and avoid agglomeration. When the acid solution is an oxidizing acid, that is, the acid solution is hypochlorous acid or sulfuric acid, it can partially oxidize cellulose, increase its hydrolysis rate, and promote the shearing of biomass cell walls. When the acid solution is an organic acid, that is, the acid solution is acetic acid or citric acid, a complex can be formed on the cellulose surface to improve the uniformity of the microporous structure after carbonization. When the acid solution is sulfuric acid or phosphoric acid, it can promote the degradation of lignin, reduce the collapse of the carbon skeleton during high temperature carbonization, and form an appropriate amount of micropores. When the acid solution is acetic acid or citric acid, it can regulate the growth of the carbon skeleton, inhibit the excessive specific surface area, and improve the cycle stability. The acid solution in this embodiment can be selected according to the needs of the corresponding acid solution, which is not limited to this.

[0040] In a further embodiment, the pH of the first mixed solution is any value in the range of 1.0-3.0, that is, the pH of the first mixed solution can be 1.0, 1.5, 2.0, 2.5 or 3.0, or any value in the range of 1.0-3.0. In a strongly acidic environment with a pH of 1.0-3.0, the acid solution in the low eutectic solvent provides a stronger hydrogen bonding effect, making the low melting point metal chloride more stable as a hydrogen bond acceptor, and the high melting point metal nitrate can maintain a higher solubility, avoiding the formation of hydroxide precipitation, so that the viscosity of the low eutectic solvent is reduced, the fluidity is enhanced, and the solubility is improved, so that it can more effectively penetrate and act on the biomass raw materials, improve its shear and solubility, further weaken the hydrogen bond network of cellulose, reduce the crystallinity, thereby reducing the collapse of amorphous carbon, making the hard carbon structure more uniform, and improving the cycle stability.

[0041] In a further embodiment, the following steps are also included before step S300: The second mixed solution is mechanically activated by high-energy ball milling, and the mechanical activation time is any value in the range of 0.1h-6h.

[0042] In this embodiment, before filtering and drying the second mixed solution, the second mixed solution needs to be mechanically activated. The mechanical activation method can significantly reduce the particle size of the biomass raw material in the second mixed solution, increase the specific surface area, thereby providing more active sites, enhancing the reaction activity of the biomass raw material, reducing the activation energy, making the reaction more uniform, and the product performance more stable, which can greatly increase the reaction rate and shorten the process flow.

[0043] In this embodiment, the densely packed metal nanoparticles in the first mixed solution can be embedded in the hydrogen bond network structure of the highly conductive cellulose through mechanical activation, which can significantly improve the electrochemical performance of the hard carbon negative electrode material. The densely packed structure of the metal nanoparticles not only provides abundant active sites, but also forms a continuous electronic conduction network, which greatly promotes the rapid transmission of electrons and ions. This structural design effectively reduces the charge transfer impedance, maximizes the utilization rate of metal active substances, and makes it show higher efficiency in electrochemical reactions. In addition, the nanoporous structure of the hard carbon negative electrode material plays an important role in the cycle process, not only providing sufficient channels for the penetration of electrolytes and ion diffusion, but also effectively alleviating the stress concentration problem caused by the volume change of metal nanoparticles during the charge and discharge process. Through this buffering effect, the structural integrity of the hard carbon negative electrode material is maintained, thereby significantly enhancing its rate performance and cycle stability.

[0044] In this embodiment, the ball-to-material ratio of the high-energy ball milling method is any value in the range of 0.1-10:1, and the ball milling speed is any value in the range of 100rpm-500rpm, that is, the ball-to-material ratio can be 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 5:1, 7:1, or 10:1, or any value in the range of 0.1-10:1, and the ball milling speed can be 100rpm, 150rpm, 200rpm, 300rpm, 400rpm or 500rpm, or any value in the range of 100rpm-500rpm. By setting the ball-to-material ratio and the ball milling speed in the above ranges, the uniformity of particle distribution in the second mixed solution is improved, the specific surface area is increased, and the sodium ion storage performance of the hard carbon negative electrode material is optimized.

[0045] In a further embodiment, the biomass raw material is any one or more of bamboo, wood, reed, coffee grounds, bagasse, cotton stalk, hemp stalk, wheat straw, rice straw, corn stalk, corn cob, coconut shell, durian shell, rice husk, walnut shell, peanut shell, hazelnut shell, starch, and lignin. The biomass raw materials involved in this embodiment come from a wide range of sources, covering different types such as lignocellulose, herbaceous cellulose, fruit shells, agricultural waste, and single-component organic matter (starch, lignin). Due to the different chemical compositions, microstructures, and ash contents of different biomass raw materials, they have their own characteristics in the preparation process of hard carbon negative electrode materials in terms of specific capacity, pore structure, conductivity, cycle stability, and other electrochemical properties. By rationally selecting and optimizing biomass raw materials, comprehensive technical effects such as high specific capacity, high first coulomb efficiency, long cycle life, and excellent rate performance can be achieved in sodium storage hard carbon materials.

[0046] In a further embodiment, the mass ratio of the biomass raw material to the first mixed solution in the second mixed solution is any value in the range of 0.01-5:1, that is, the mass ratio of the biomass raw material to the first mixed solution can be 0.01:1, 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 3:1, 4:1 or 5:1, or any value in the range of 0.01-5:1. In this embodiment, by setting the mass ratio of the biomass raw material to the first mixed solution in the second mixed solution within the above ratio range, it is possible to ensure that the biomass is completely infiltrated, maintain the uniformity and solubility of the low eutectic solvent system, ensure that the biomass is fully reacted, avoid excessive degradation or insufficient modification, and improve the microstructural uniformity of the hard carbon material. At the same time, the metal chloride and the high melting point metal nitrate can be evenly dispersed and form a metal coordination complex inside the biomass structure, ensuring the uniform etching of the metal in the subsequent carbonization process, improving the controllability of the pore structure of the carbon material, improving the specific capacity, reducing metal residues, improving the electrochemical stability of the electrode, and improving the cycle life.

[0047] The present invention also provides a biomass-based hard carbon negative electrode material, which is prepared according to the preparation method of the hard carbon negative electrode material.

[0048] The present invention also provides a sodium ion battery, including a hard carbon negative electrode material prepared by the preparation method of the hard carbon negative electrode material, wherein the first discharge specific capacity of the sodium ion battery is higher than 389 mAh / g, the first coulombic efficiency is greater than 94.5%, and the capacity retention rate after 2000 cycles is higher than 92.25%. The preparation method of the hard carbon negative electrode material will not be described in detail here. In this embodiment, by using the hard carbon negative electrode material prepared by the above preparation method as the negative electrode material of the sodium ion battery, the discharge specific capacity, first coulombic efficiency and rate performance of the sodium ion battery can be significantly improved.

[0049] In this embodiment, in the preparation method of the sodium ion battery, the hard carbon negative electrode material prepared in the above embodiment is used as the negative electrode active material. The negative electrode active material, the conductive agent, the first adhesive and the second adhesive are weighed according to the mass ratio of 95:2:2:1, and then deionized water is added and stirred for 6 hours to obtain a uniform black slurry. The black slurry is in a viscous slurry state. The above black slurry is evenly coated on the copper foil, and then vacuum dried at 80°C for 12 hours to obtain a pole piece with uniform thickness, and then the pole piece is punched into a disc with a diameter of 14 mm as the negative electrode. A metal disc with a diameter of 14 mm is used as the negative electrode, glass fiber is used as the diaphragm, and 1 mol / L NaPF6 is used as the electrolyte. A CR2025 button battery is assembled in a glove box filled with argon gas, and the battery is left to stand for 24 hours before the charge and discharge performance test is performed. Here, the conductive agent is acetylene black, the first adhesive is sodium carboxymethyl cellulose, and the second adhesive is styrene-butadiene rubber.

[0050] The present application will be further described in detail below with reference to specific embodiments.

[0051] Example 1 In the preparation method of the hard carbon negative electrode material in this embodiment, tin chloride, molybdenum nitrate and acetic acid are first dissolved in water in a molar ratio of 0.5:0.1:5:1, and a first mixed solution is obtained after stirring. Then bamboo powder is added to the first mixed solution, wherein the mass ratio of bamboo powder to the first mixed solution is 0.1:1, and then the second mixed solution is mechanically activated at a speed of 300 rpm for 30 minutes, and the ball-to-material ratio of mechanical activation is 3:1. The product after mechanical activation is filtered and dried at 80°C to obtain a pretreated biomass precursor. The obtained biomass precursor is heated to 800°C at 5°C / min in a tubular furnace in a nitrogen atmosphere and kept warm for 0.5h, and then heated to 1300°C at 3°C / min and kept warm for 3h, and then cooled with the furnace, and finally the calcined product is taken out and crushed and sieved to obtain a hard carbon negative electrode material for sodium ion batteries.

[0052] Example 2 In the preparation method of the hard carbon negative electrode material in this embodiment, zinc chloride, molybdenum nitrate and phosphoric acid are first dissolved in water in a molar ratio of 5:10:5:1, and a first mixed solution is obtained after stirring. Then bamboo powder is added to the first mixed solution, wherein the mass ratio of bamboo powder to the first mixed solution is 0.5:1, and then mechanical activation is performed at a speed of 500 rpm for 10 minutes, and the ball-to-material ratio of mechanical activation is 3:1. The product after mechanical activation is filtered and dried at 80°C to obtain a pretreated biomass precursor. The obtained biomass precursor is heated to 600°C at 5°C / min in a tubular furnace in a nitrogen atmosphere and kept warm for 2 hours, and then heated to 1600°C at 3°C / min and kept warm for 1 hour, and then cooled with the furnace. Finally, the calcined product is taken out and crushed and sieved to obtain a hard carbon negative electrode material for a sodium ion battery.

[0053] Example 3 In the preparation method of the hard carbon negative electrode material in this embodiment, aluminum chloride, ferric nitrate and acetic acid are first dissolved in water in a molar ratio of 0.01:0.05:0.1:1, and a first mixed solution is obtained after stirring. Then bamboo powder is added to the first mixed solution, wherein the mass ratio of bamboo powder to the first mixed solution is 0.01:1, and then mechanical activation is performed at a speed of 100 rpm for 6 hours, and the ball-to-material ratio of mechanical activation is 5:1. The product after mechanical activation is filtered and dried at 80°C to obtain a pretreated biomass precursor. The obtained biomass precursor is heated to 400°C at 3°C / min in a tubular furnace in a nitrogen atmosphere and kept warm for 2 hours, and then heated to 1100°C at 2°C / min and kept warm for 12 hours, and then cooled with the furnace. Finally, the calcined product is taken out and crushed and sieved to obtain a hard carbon negative electrode material for sodium ion batteries.

[0054] Example 4 In the preparation method of the hard carbon negative electrode material in this embodiment, zinc chloride, molybdenum nitrate and formic acid are first dissolved in water in a molar ratio of 0.5:0.001:10:1, and a first mixed solution is obtained after stirring. Then coconut shell powder is added to the first mixed solution, wherein the mass ratio of coconut shell powder to the first mixed solution is 5:1, and then mechanical activation is performed at a speed of 300 rpm for 30 minutes, and the ball-to-material ratio of mechanical activation is 10:1. The product after mechanical activation is filtered and dried at 80°C to obtain a pretreated biomass precursor. The obtained biomass precursor is heated to 800°C at 5°C / min in a tubular furnace in a nitrogen atmosphere and kept warm for 0.5h, and then heated to 1500°C at 3°C / min and kept warm for 3h, and then cooled with the furnace. Finally, the calcined product is taken out and crushed and sieved to obtain a hard carbon negative electrode material for sodium ion batteries.

[0055] Example 5 In the preparation method of the hard carbon negative electrode material in this embodiment, tin chloride, cobalt nitrate and acetic acid are first dissolved in water in a molar ratio of 0.5:0.05:2:1, and a first mixed solution is obtained after stirring. Then coconut shell powder is added to the first mixed solution, wherein the mass ratio of coconut shell powder to the first mixed solution is 0.05:1, and then mechanical activation is performed at a speed of 300 rpm for 60 minutes, and the ball-to-material ratio of mechanical activation is 0.1:1. The product after mechanical activation is filtered and dried at 80°C to obtain a pretreated biomass precursor. The obtained biomass precursor is heated to 500°C at 5°C / min in a tubular furnace in a nitrogen atmosphere and kept warm for 6 hours, and then heated to 1300°C at 3°C / min and kept warm for 2 hours, and then cooled with the furnace. Finally, the calcined product is taken out and crushed and sieved to obtain a hard carbon negative electrode material for sodium ion batteries.

[0056] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the first mixed solution is a composition of acetic acid and water, and the molar ratio of acetic acid to water is 5:1. The pretreated biomass precursor is directly heated to 1300°C and kept warm for 3 hours to prepare a hard carbon negative electrode material for a sodium ion battery.

[0057] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the first mixed solution does not include tin chloride.

[0058] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is only that the first mixed solution does not include platinum nitrate.

[0059] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the second mixed solution is not mechanically activated but only stirred.

[0060] The hard carbon negative electrode materials prepared in Examples 1-5 and Comparative Examples 1-4 were used as negative electrode active materials of corresponding sodium ion batteries, and the electrochemical performance of the sodium ion batteries prepared based on the hard carbon negative electrode materials prepared in Examples 1-5 and Comparative Examples 1-4 was tested to obtain the electrochemical performance test result graph shown in Table 1. Here, the test temperature in the electrochemical performance test is 25° C., and the charge and discharge cut-off voltage is 0.01-2.5V.

[0061]

[0062] As shown in Table 1, the hard carbon negative electrode materials prepared in Examples 1-5 as negative electrode active materials of sodium ion batteries can make the corresponding sodium ion batteries have a first charge specific capacity higher than 389 mAh / g, a first coulomb efficiency higher than 94%, a first discharge specific capacity higher than 349 mAh / g at a current density of 1 A / g, and a capacity retention rate higher than 92% after 2000 cycles at a current density of 1 A / g. Compared with the hard carbon negative electrode materials prepared as negative electrode active materials of sodium ion batteries by pretreating the biomass raw materials with acid solution only in Comparative Example 1, the first mixed solution in Comparative Example 2 does not include a low melting point metal chloride, the first mixed solution in Comparative Example 3 does not include a high melting point metal nitrate, and the second mixed solution in Comparative Example 4 is not mechanically activated, the sodium ion batteries prepared by the hard carbon negative electrode materials prepared in Examples 1-5 of the present invention all have significantly improved discharge specific capacity, first coulomb efficiency and rate performance, that is, the hard carbon negative electrode materials prepared by the one-time pyrolysis method of the present invention have the advantages of high first efficiency, low cost, high capacity and long life.

[0063] Figure 2 is the XRD spectrum of the hard carbon negative electrode material prepared according to Example 1 of the present invention, Figure 3 is a SEM image of the hard carbon negative electrode material prepared according to Example 1 of the present invention, Figure 4 is the first cycle discharge curve of the sodium ion battery of the hard carbon negative electrode material prepared according to Example 1 of the present invention, Figure 5 is the first cycle discharge curve of the sodium ion battery of the hard carbon negative electrode material prepared in Comparative Example 1 of the present invention, Figure 6 is the first cycle discharge curve of the sodium ion battery of the hard carbon negative electrode material prepared according to Comparative Example 2 of the present invention, Figure 7 This is the first cycle discharge curve of the sodium ion battery using the hard carbon negative electrode material prepared in Comparative Example 4 of the present invention.

[0064] like Figure 2 As shown, the XRD spectrum of the hard carbon negative electrode material prepared in Example 1 includes two peak positions, (002) and (100), wherein the position of the (002) peak appears at 2θ=26°, and the corresponding interlayer spacing is about 3.4Å, and the position of the (100) peak appears at 2θ=45°, indicating that the material of the product prepared in Example 1 is hard carbon, and the peak intensity ratio of the (002) peak to the (100) peak is 2, that is, the (002) peak intensity is higher and the (100) peak intensity is weaker, indicating that the crystal layer structure of the sample is more layered and neatly stacked, and there is a strong diffraction signal in the direction perpendicular to the layer, indicating that the atomic arrangement in the plane is relatively irregular or disordered. The peak intensity ratio of 2 further indicates the orderliness of the interlayer arrangement of the hard carbon negative electrode material prepared in Example 1, that is, the product prepared in Example 1 has a certain degree of graphitization, and the hard carbon negative electrode material is successfully prepared.

[0065] like Figure 3 As shown, the hard carbon negative electrode material prepared in Example 1 has a porous honeycomb structure, that is, the biomass precursor obtained by pretreatment is transformed from a submicron cluster structure composed of neatly arranged fibers into a unique porous honeycomb structure, so that during the high-temperature carbonization process, the biological precursor with a porous honeycomb structure can form more abundant closed pores, thereby increasing the sodium storage sites of the hard carbon negative electrode material and improving the platform capacity.

[0066] like Figure 4 As shown, Figure 4 It is the charge and discharge curve of Example 1. The charge curve and discharge curve of the hard carbon negative electrode material prepared in Example 1 both show a high-voltage slope area and a low-voltage platform-like area, and the charge specific capacity and discharge specific capacity can both reach 400mAh / g, which indicates that more cellulose is dissolved by pretreatment with a low eutectic solvent system, and more optimized nanopore structures are formed in the carbon material in combination with high-melting-point nitrates, which increases the specific surface area while reducing structural defects, thereby further etching the hard carbon negative electrode material. More nanopore structures are more conducive to the storage of sodium ions.

[0067] like Figure 5 As shown, the charge and discharge curves of the products prepared in Comparative Example 1 do not have any low-voltage platform-like region, indicating that Comparative Example 1 only uses acid solution to pretreat the biomass raw materials and cannot completely hydrolyze the biomass raw materials, resulting in the product after subsequent calcination not being graphitized hard carbon.

[0068] like Figure 6 and Figure 7 As shown, in the charge and discharge curves of the products prepared in Comparative Examples 2 and 4, although there are quasi-platform areas in the low voltage zone, the discharge specific capacities in Comparative Examples 2 and 4 are both lower than 362 mAh / g, that is, when there is a lack of low-melting-point metal chloride in the first mixed solution or the second mixed solution is not mechanically activated, the biomass raw material cannot be completely hydrolyzed to form cellulose.

[0069] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0070] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a biomass-based hard carbon negative electrode material, characterized in that: The steps include: Prepare a first mixed solution, wherein the first mixed solution includes a low melting point metal chloride, a high melting point metal nitrate, an acid solution and an aqueous solvent, and the pH of the first mixed solution is any value between 1.0 and 5.0; Adding the biomass raw material to the first mixed solution and mixing them evenly to prepare a second mixed solution; The second mixed solution is filtered and dried in sequence to prepare a biomass precursor; The biomass precursor is placed in an inert protective gas and calcined in stages, and the calcined products are crushed and sieved in sequence to prepare the hard carbon negative electrode material; wherein: The low melting point metal chloride and the acid solution form a low eutectic solvent system, the melting point of the metal ions in the low melting point metal chloride is lower than 650°C, the melting point of the metal ions in the high melting point metal nitrate is higher than 1100°C, and the calcination temperature of the staged calcination includes a first temperature and a second temperature, the first temperature is any value between 400°C and 800°C, and the second temperature is any value between 1100°C and 1600°C.

2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The low melting point metal chloride salt is any one or more of tin chloride, zinc chloride, gallium chloride, aluminum chloride, sodium chloride, potassium chloride, and lead chloride; The high melting point metal nitrate is any one or more of titanium nitrate, zirconium nitrate, molybdenum nitrate, vanadium nitrate, chromium nitrate, niobium nitrate and iron nitrate.

3. The method for preparing a hard carbon negative electrode material according to claim 2, characterized in that: The molar ratio of the low melting point metal chloride, the high melting point metal nitrate, the acid solution and the water solvent in the first mixed solution is any value of (0.01-5):(0.001-10):(0.1-10):

1.

4. The method for preparing a hard carbon negative electrode material according to claim 3, characterized in that: The acid solution is any one or more of hypochlorous acid, hydrochloric acid, sulfuric acid, sulfurous acid, acetic acid, formic acid, citric acid, and phosphoric acid.

5. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The pH of the first mixed solution is any value between 1.0 and 3.

0.

6. The method for preparing a hard carbon negative electrode material according to claim 5, characterized in that: Before the step of sequentially filtering and drying the second mixed solution to prepare the biomass precursor, the following step is also included: The second mixed solution is mechanically activated by high-energy ball milling, and the mechanical activation time is any value in the range of 0.1 h to 6 h.

7. The method for preparing a hard carbon negative electrode material according to any one of claims 1 to 6, characterized in that: The biomass raw material is any one or more of bamboo, wood, reed, coffee grounds, bagasse, cotton stalks, hemp stalks, wheat straw, rice straw, corn stalks, corn cobs, coconut shells, durian shells, rice husks, walnut shells, peanut shells, hazelnut shells, starch, and lignin.

8. The method for preparing a hard carbon negative electrode material according to claim 7, characterized in that: The mass ratio of the biomass raw material in the second mixed solution to the first mixed solution is any value in the range of 0.01-5:

1.

9. A biomass-based hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material is prepared according to the preparation method of any one of claims 1-8.

10. A sodium ion battery, characterized in that: A hard carbon negative electrode material prepared by the preparation method of a hard carbon negative electrode material according to any one of claims 1 to 8, wherein the first discharge specific capacity of the sodium ion battery is higher than 389 mAh / g, the first coulombic efficiency is greater than 94.5%, and the capacity retention rate after 2000 cycles is higher than 92.25%.

Citation Information

Patent Citations

  • Cathode material for lithium-ion power and energy storage battery and preparation method thereof

    CN101916856A

  • Preparation method and application of waste biomass derived graphene material

    CN112707386A

  • Preparation method of high-yield biomass-based sodium ion battery hard carbon negative electrode material

    CN118343735A

  • Production of carbon- or graphite-based anode active materials from biomass feedstock

    US20240367980A1

Cited By

  • Sn-Fe bimetal doped rice hull catalyst and preparation method and application thereof

    CN120502332A

  • A Sn-Fe bimetallic doped rice husk catalyst, its preparation method and application

    CN120502332B

  • Bio-based hard carbon for negative electrode material and preparation method of bio-based hard carbon

    CN121202115A

  • A bio-based hard carbon for an anode material and a preparation method thereof

    CN121202115B